ANALISIS HUKUM ISLAM TERHADAP PRAKTIK KREDIT PAKAIAN DI PASAR TRADISIONAL ABAI SIAT KECAMATAN KOTO BESAR KABUPATEN DHARMASRAYA - Wilaga Saputra; Johan Agustian; Lesis Andre; Susi Puspita Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the widespread practice of clothing credit transactions among lower-middle-class communities at the Abai Siat Traditional Market. Credit systems are seen as a solution for meeting clothing needs amid economic limitations. However, from an Islamiclegal perspective, such practices require further analysis, as they may involve elements ofgharar (uncertainty), riba (usury), and violations of Sharia principles. The aim of thisresearch is to understand how clothing credit is implemented and assess its compliancewith Islamic law. The research uses a qualitative descriptive method with an empiricallegal approach. Data collection was conducted through direct observation, interviews withfive clothing vendors, five credit users (buyers), and three local religious figures, alongwith supporting documentation. This approach aims to explore the social reality of creditpractices and evaluate their alignment with Islamic commercial law (muamalah). Findingsindicate that three out of five vendors applied Sharia-compliant credit systems, with clearcontracts (akad), maximum repayment periods of two to three installments, fixed prices forboth cash and credit purchases, and mutual consent from both parties. Meanwhile, twovendors showed indications of non-compliance with Islamic principles, especially due tothe absence of clear payment terms and lack of written agreements—conditions that fallunder gharar. In conclusion, clothing credit practices that are clear, fair, and transparent,and follow the legal requirements of Islamic transactions, are permissible and beneficial.However, practices involving uncertainty need to be improved to ensure they do notviolate Sharia principles or harm either party involved.